2022
DOI: 10.1111/psyg.12830
|View full text |Cite
|
Sign up to set email alerts
|

A first insight into the clinical manifestation of posttraumatic stress disorder in dementia: a systematic literature review

Abstract: Posttraumatic stress disorder (PTSD) is a prevalent disorder worldwide and often co‐occurs in dementia. Both have a major impact on disease burden and quality of life. PTSD may be difficult to recognize in dementia and a structured diagnostic method is lacking. In order to get insight into the clinical diagnostics of PTSD in dementia, this systematic literature review evaluates the clinical presentation of PTSD and other relevant symptoms in people with dementia. PubMed, PsycINFO, Embase, and CINAHL were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…The case reports show positive effects on the symptoms measured or described, such as fewer flashbacks, more acceptance of the past and less restlessness 24,27,28 . Positive effects of EMDR on neuropsychiatric symptoms often associated with challenging behaviour of dementia can reflect the alternative clinical presentation of PTSD in people with dementia, showing symptoms such as screaming 16 . These case reports indicate that EMDR might be also feasible and effective for reducing PTSD symptoms in people with dementia.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The case reports show positive effects on the symptoms measured or described, such as fewer flashbacks, more acceptance of the past and less restlessness 24,27,28 . Positive effects of EMDR on neuropsychiatric symptoms often associated with challenging behaviour of dementia can reflect the alternative clinical presentation of PTSD in people with dementia, showing symptoms such as screaming 16 . These case reports indicate that EMDR might be also feasible and effective for reducing PTSD symptoms in people with dementia.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, people with dementia and PTSD can show a variety of symptoms often associated with neuropsychiatric symptoms of dementia and not as symptoms of PTSD 14 . Examples are verbal agitation, physical aggression, flashbacks, fear and nightmares 15,16 . For neuropsychiatric symptoms seen in people with dementia the treatment options reported are broad with low grades of evidence 17 .…”
Section: Introductionmentioning
confidence: 99%
“…A shared limitation in diagnosing PTSD using the ICD-11 and DSM-5 is the required presence of one of the core elements 'avoidance symptoms', which a literature review show are not recognized in people with dementia. 23,49 The development of the TRADE-interview has added value for both clinical practice and research. The TRADEinterview offers opportunities to conduct methodologically solid and consistent research into this complex target group.…”
Section: Discussionmentioning
confidence: 99%
“…43 This can be explained by case reports in the literature that indicate that criterion C (avoidance symptoms) were rarely reported. 23 , 49 Notably, most sub-criteria of criterion D (negative cognition and mood symptoms) were excluded in the TRADE-interview because they are indistinguishable from BPSD. Most experts indicated that before such cut-offs should and could be considered, actual testing and observation in practice should take place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation